Enrichment and immobilization of quinone-respiring bacteria in anaerobic granular sludge - Cervantes, F J (Water science and technology : a journal of the International Association on Water Pollution Research, 2003)
The capacity of an anaerobic granular sludge for serving as an immobilizing mechanism for quinone-respiring bacteria was evaluated. The inoculum was continuously fed with a basal medium containing the humic model compound, anthraquinone-2,6-disulfonate (AQDS), as a terminal electron acceptor. Complete reduction of AQDS was achieved by the granular sludge for a prolonged period in an anaerobic bioreactor provided with a mixture of volatile fatty acids as a substrate. Phylogenetic analysis revealed the enrichment and immobilization of AQDS-respiring bacteria appearing as dominant organisms in the microbial population of the AQDS-supplemented reactor, compared to a reactor control operated under methanogenic conditions. The consistent quinone-reducing capacity observed in the consortium indicates that it is feasible to apply quinone-reducing microorganisms in continuous bioreactors and this ability can potentially be important in wastewaters rich in humic substances. The quinone reducing activity could also be applied to accelerate the conversion of xenobiotics susceptible to reductive biotransformations such as azo dyes and polychlorinated compounds in continuous bioreactors